Integrating collaborative learning and realistic mathematics education throught techonology enhanced student worksheets - Tali Wangge, Maria Carmelita; Bhoke, Wilibaldus; Vilmit Ndao, Yosefa; Kapoh, Jeane Rosalia; Lujur, Veronika; Bai Rema, Iventius; Megu, Bonifasius (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to develop and validate technology-enhanced student worksheets that integrate collaborative learning and Realistic Mathematics Education (RME) to support meaningful mathematics learning at the junior high school level. The study responds to the need for instructional materials that move beyond routine exercises by fostering conceptual understanding, collaborative problem-solving, and students’ ability to connect mathematical concepts with real-life contexts. Method: This research employed a design-based research approach within a Research and Development framework. The development process consisted of six stages: needs analysis, instructional design, expert validation, limited classroom trials, product revision, and implementation. The participants included junior high school students and mathematics teachers. Data were collected using expert validation sheets, classroom observation protocols, student response questionnaires, and assessments of learning outcomes. Qualitative and descriptive quantitative analyses were used to evaluate the validity, practicality, and effectiveness of the developed worksheets. Findings: The findings indicate that the technology-enhanced collaborative worksheets demonstrate a high level of validity in terms of content relevance, instructional structure, and language clarity. Results from classroom trials show increased student engagement, improved collaborative interaction, and enhanced mathematical understanding, particularly in problem-solving and mathematical communication. Students were able to actively participate in group discussions and construct mathematical knowledge through contextual learning activities. Significance: This study contributes to mathematics education by providing empirically grounded instructional materials that integrate collaborative learning, RME principles, and technology-enhanced design. The findings offer practical implications for educators and curriculum developers in designing student-centered mathematics learning resources and support the broader application of design-based research in mathematics education.